Comportamiento reproductivo ovino en una región alta de Colombia (1978)
The reproductive performance of the ewe was studied in San Jorge Farm, situated between 2.800 and 3.300 meters above sea level, 400 - 30' latitude N and 740 - 12' W of Greenwich meridiam. The studies were named: "Comparison of breeding seasons", "Effect of teasing and flushing in ewe oestrus", "Age at first oestrus of ewe Lambs" and "Mating ewes all the year round". The results have shown that oestrus ocurred all the year round and that ewe lambs experienced their first heat between four and eight months of age; there was no correlation between the oestrus ocurrence on one hand and the age or live weight on the other. The conception rate was influence neither by vasectomized rams nor by flushing. Three crops of Lambs were obtained during two years by the ewes running with rams all the year round, but it was achieved only with a third of the ewes envolved.